2016
DOI: 10.1080/10253890.2016.1192603
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress impairs cognitive flexibility in men, not women

Abstract: Psychosocial stress influences cognitive abilities such as long-term memory retrieval. However, less is known about the effects of stress on cognitive flexibility, which is mediated by different neurobiological circuits and could thus be regulated by different neuroendocrine pathways. In this study we randomly assigned healthy adults to an acute stress induction or control condition and subsequently assessed participants’ cognitive flexibility using an open-source version of the Wisconsin Card Sort task. Drawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 20 publications
8
53
1
1
Order By: Relevance
“…E. Miller, Chen, & Parker, 2011;Myin-Germeys, Krabbendam, Delespaul, & Van Os, 2003;Silverman & Sternberg, 2012;Slavich & Irwin, 2014). Greater stress exposure can also impair cognitive function (Shields, Sazma, & Yonelinas, 2016;Shields, Trainor, Lam, & Yonelinas, 2016)-presumably degrading quality of life (Diamond, 2013)-and is a strong predictor of earlier mortality (Rosengren et al, 1993). Multiple models have been proposed to account for these findings, and these models have been discussed in several excellent reviews (e.g., Doom & Gunnar, 2013;Heim & Binder, 2012;Hostinar & Gunnar, 2013;Koenig, Walker, Romeo, & Lupien, 2011;McEwen, 1998;Nederhof & Schmidt, 2012).…”
Section: Stress Its Definition and Relevance For Healthmentioning
confidence: 99%
“…E. Miller, Chen, & Parker, 2011;Myin-Germeys, Krabbendam, Delespaul, & Van Os, 2003;Silverman & Sternberg, 2012;Slavich & Irwin, 2014). Greater stress exposure can also impair cognitive function (Shields, Sazma, & Yonelinas, 2016;Shields, Trainor, Lam, & Yonelinas, 2016)-presumably degrading quality of life (Diamond, 2013)-and is a strong predictor of earlier mortality (Rosengren et al, 1993). Multiple models have been proposed to account for these findings, and these models have been discussed in several excellent reviews (e.g., Doom & Gunnar, 2013;Heim & Binder, 2012;Hostinar & Gunnar, 2013;Koenig, Walker, Romeo, & Lupien, 2011;McEwen, 1998;Nederhof & Schmidt, 2012).…”
Section: Stress Its Definition and Relevance For Healthmentioning
confidence: 99%
“…Even so, one study in humans (Shields et al, 2016b) and another in rodents (Laredo et al, 2015) found that stress-induced impairments of cognitive flexibility are greater for males than females. Although the reason for this sex difference is not completely clear, this sex difference appears to be mediated by sex differences in μ-opioid receptor binding in the orbitofrontal cortex following stress (Laredo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study only included healthy young men; for this reason, the present results cannot be readily generalized to women. There are few studies on acute stress and response inhibition or other core executive functions comprising both male and female participants, some of which did not report sex differences (e.g., Schwabe et al, 2013;Plessow et al, 2012), while others found women and men to be differently affected (e.g., Schoofs et al, 2013;Shields, Trainor, Lam, & Yonelinas, 2016). As well, sex differences in the stress response are known (e.g., Kajantie & Phillips, 2006), and there is at least some evidence for sex differences in response inhibition and its neural correlates (e.g., Omura & Kusumoto, 2015).…”
mentioning
confidence: 99%